Lightweight concrete and preparation method thereof

Through the combination of raw materials in a specific proportion and the use of modified reinforcement fibers and foam stabilizers, the shortcomings of lightweight concrete in foam distribution, stability, toughness and compressive strength are solved, and high-performance lightweight concrete is achieved.

CN119735405APending Publication Date: 2025-04-01SHANDONG HONGYI TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411931523.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Existing lightweight concrete has shortcomings in uneven foam distribution, poor stability, insufficient toughness, easy cracking, low compressive strength and poor insulation effect, which is difficult to meet the high requirements of building materials for comprehensive performance.

Method used

Lightweight concrete is prepared using specific proportions of raw materials, including cement, fly ash, ceramic granules, light aggregates, modified reinforcement fibers, modified coal gangue, foaming agent and foam stabilizing agent. Through the combination of modified reinforcement fibers and foam stabilizing agents, the foam stability and the mechanical properties of concrete are improved.

Benefits of technology

Lightweight concrete with uniform foam distribution, strong stability, good toughness, no easy cracking, high compressive strength and good insulation effect are achieved, and its comprehensive performance is significantly better than traditional methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735405A_ABST
    Figure CN119735405A_ABST
Patent Text Reader

Abstract

The present invention discloses a lightweight concrete and a preparation method thereof, and belongs to the technical field of lightweight concrete. The lightweight concrete of the present invention is prepared from the following raw materials by weight: 200-300 parts of cement, 15-25 parts of fly ash, 60-80 parts of ceramsite, 50-60 parts of lightweight aggregate, 60-100 parts of modified reinforcing fiber, 70-90 parts of modified coal gangue, 20-30 parts of foaming agent, 15-20 parts of foam stabilizer, and 150-200 parts of water. The present invention creatively uses 5 kinds of non-ionic surfactants to prepare the foaming agent and then synergizes with the foam stabilizer to effectively improve the foam stability; and the reinforcing fiber is modified to effectively improve the compressive strength and flexural strength of the concrete. The lightweight concrete prepared by the present invention has excellent comprehensive performance, has uniform foam distribution, strong foam stability, good toughness, is not easy to crack, has high strength, and has good thermal insulation effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lightweight concrete, and particularly relates to lightweight concrete and a preparation method thereof. Background Art

[0002] Modern civil engineering constantly places new demands on the quality, energy efficiency and fire safety of structural components. One of the solutions to these demands is the use of lightweight concrete. The basic characteristics of lightweight concrete are its lower bulk density and better thermal insulation properties, which is an important difference from ordinary concrete. Today, concrete, as a modern composite material, is not only considered as a building material, but also as a thermal insulation material or aesthetic building finish. From an earthquake point of view, lightweight aggregate concrete has the advantage of low deadweight. In addition, lightweight aggregates are usually expansive materials and are therefore very effective for sound and heat insulation. Partial or total replacement of ordinary mass concrete with lightweight aggregate concrete can produce considerable benefits by reducing the dead load of the structure.

[0003] The main preparation methods of lightweight concrete include foaming method, filling method and other preparation methods. Foamed concrete, also known as air concrete, is made by introducing a foaming agent to foam. It has low density, light weight, excellent thermal insulation performance, good sound insulation and noise reduction performance, superior seismic performance and other excellent properties, but its compressive strength is low. Filled lightweight concrete includes EPS concrete, HGMS concrete, ceramsite ball concrete, plastic concrete, etc. Although these materials meet certain applications in terms of density, the mechanical strength, durability and other properties of the composite materials are poor. In actual application, it is necessary to select a suitable mix ratio according to construction requirements. Foamed concrete made by adding a foaming agent to concrete can be quickly prepared and is convenient for construction. The voids in the matrix of foamed concrete reduce its thermal conductivity and dry density. However, due to its reduced density, foamed concrete is prone to microcracks, resulting in strength loss. Summary of the invention

[0004] The object of the present invention is to provide a lightweight concrete with uniform foam distribution, strong foam stability, good toughness, not easy to crack, high strength, good thermal insulation effect and excellent comprehensive performance.

[0005] In order to achieve the above technical objectives, the technical solution adopted by the present invention is:

[0006] A lightweight concrete is prepared from the following raw materials in parts by weight: 200-300 parts of cement, 15-25 parts of fly ash, 60-80 parts of ceramsite, 50-60 parts of lightweight aggregate, 60-100 parts of modified reinforcing fiber, 70-90 parts of modified coal gangue, 20-30 parts of foaming agent, 15-20 parts of foam stabilizer and 150-200 parts of water.

[0007] Furthermore, the lightweight aggregate is pumice and volcanic slag; the expanded clay is lightweight shale expanded clay; and the cement is 42.5 grade ordinary Portland cement.

[0008] Furthermore, the preparation method of the modified reinforced fiber is:

[0009] After polyvinyl alcohol and hydroxypropyl methylcellulose ether are mixed evenly, water heated to 60° C. is poured into the mixture, stirred evenly, and then cooled to room temperature to obtain a mixture A; after steel fiber and polypropylene fiber are mixed evenly, the mixture A is added and stirred evenly, and finally barium sulfate is added and mixed evenly to obtain a modified reinforcing fiber.

[0010] Furthermore, the solid-liquid ratio of water, polyvinyl alcohol and hydroxypropyl methylcellulose ether in the mixture A is 1L:15g:10g.

[0011] Furthermore, the solid-liquid ratio of the mixture A, steel fiber, polypropylene fiber and barium sulfate is 2L:2kg:1kg:0.5kg.

[0012] Furthermore, the preparation method of the modified coal gangue is:

[0013] The coal gangue is crushed, soaked in a 2 mol / L sulfuric acid solution for 1-2 hours to remove impurities, washed with deionized water after soaking, dried, and then calcined at 800°C for 2 hours to obtain modified coal gangue.

[0014] Furthermore, the foaming agent contains 6-8 parts of lauryl glucoside, 2-5 parts of tea saponin, 3-6 parts of castor oil polyoxyethylene ether, 3-7 parts of fatty alcohol polyoxyethylene ether sulfonate, 5-8 parts of sorbitan trioleate, and 60-70 parts of water.

[0015] Furthermore, the foam stabilizer contains 5-10 parts of sodium alginate, 3-5 parts of citric acid, and 10-12 parts of cocamidopropylamine oxide.

[0016] A method for preparing lightweight concrete comprises the following steps:

[0017] S1: adding water, lauryl glucoside, tea saponin, castor oil polyoxyethylene ether, fatty alcohol polyoxyethylene ether sulfonate and sorbitan trioleate into a reaction kettle in sequence at a stirring speed of 100-150 rpm, stirring for 8-10 minutes, adding the stirred mixed solution into a pressure foaming machine, starting the pressure foaming machine for foaming, and when the foam is uniform and fine in a hook shape, the foaming agent is obtained and is ready for use;

[0018] S2: putting water, cement, ceramsite, fly ash, modified coal gangue and lightweight aggregate into a mixer and stirring to obtain cement slurry, and then adding modified reinforcing fiber and stirring to obtain mixed slurry;

[0019] S3: adding a foaming agent and a foam stabilizer to the mixed slurry of step S2, and stirring evenly to obtain a lightweight concrete.

[0020] The raw materials used in the present invention are all commercially available.

[0021] Since nonionic surfactants are not ionized, nonionic surfactants have high solubility in water or organic solvents, and are not easily affected by strong electrolyte inorganic salts and acids and alkalis in solution, and have high stability, and can be well mixed and compounded for use. Therefore, the present invention selects lauryl glucoside, tea saponin, castor oil polyoxyethylene ether, fatty alcohol polyoxyethylene ether sulfonate and sorbitan trioleate 5 kinds of nonionic surfactants to be compounded in a specific ratio to obtain a foaming agent, and 5 kinds of nonionic surfactants synergistically increase the surface viscosity of the foam liquid film, reduce the air permeability of the liquid film, improve the stability of the foam liquid film, and extend the foam life. The composite foaming agent of the present invention not only has excellent foaming effect, but also has good emulsification and foam stability, and is outstanding in environmental protection and safety, and is a multifunctional and efficient foaming agent.

[0022] The invention adopts a composite foam stabilizer composed of sodium alginate, citric acid and cocamidopropylamine oxide, so that bubbles can stably exist and be fully dispersed in the mixed material, thereby improving the density and uniformity of the mixed material and reducing the generation of pores and defects.

[0023] Polypropylene fiber can effectively control microcracks in concrete or mortar caused by factors such as plastic shrinkage, drying shrinkage, and temperature changes, prevent and inhibit the formation and development of primary cracks in concrete, and thus greatly improve the crack resistance of concrete. Steel fiber also has good crack resistance, can enhance the tensile strength of concrete, and reduce the risk of cracking under tension. Polyvinyl alcohol has a good viscosity-increasing effect, and hydroxypropyl methylcellulose ether can improve the bonding force between fiber and mortar, so that the fiber can be quickly and firmly bonded to various materials, enhance the crack resistance of concrete, and play a moisturizing role. Barium sulfate particles have a large surface area and strong adsorption capacity, which can adjust the fluidity and bonding between fiber and cement slurry, making construction more convenient and stable.

[0024] Beneficial Effects

[0025] The foaming agent and the foam stabilizer cooperate with each other to obtain concrete with high foam uniformity, moderate independent foam consistency, complete foam and slow defoaming, which is beneficial to improving the compressive strength of concrete and improving thermal insulation performance.

[0026] The reinforcing fibers of the present invention are compounded with steel fibers and polypropylene fibers, and then the steel fibers and polypropylene fibers are modified by polyvinyl alcohol, hydroxypropyl methylcellulose ether and barium sulfate, which can significantly improve the interface adhesion between the reinforcing fibers and other materials, thereby improving the mechanical properties of lightweight concrete.

[0027] The lightweight concrete prepared by the invention has the characteristics of uniform foam distribution, strong foam stability, good toughness, not easy to crack, high strength, good thermal insulation effect, and excellent comprehensive performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The SEM images of the samples of Example 3 and Comparative Examples 1-4 of the present invention are shown. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is further described below in conjunction with specific embodiments, but is not limited thereto.

[0030] Example 1

[0031] A lightweight concrete is prepared from the following raw materials in parts by weight: 200 parts of cement, 15 parts of fly ash, 60 parts of ceramsite, 50 parts of lightweight aggregate, 60 parts of modified reinforcing fiber, 70 parts of modified coal gangue, 20 parts of foaming agent, 15 parts of foam stabilizer, and 150 parts of water.

[0032] The lightweight aggregate is pumice and volcanic slag; the expanded clay is lightweight shale expanded clay; and the cement is 42.5 grade ordinary Portland cement.

[0033] The preparation method of the modified reinforced fiber is:

[0034] After polyvinyl alcohol and hydroxypropyl methylcellulose ether are mixed evenly, water heated to 60° C. is poured into the mixture, stirred evenly, and then cooled to room temperature to obtain a mixture A; after steel fiber and polypropylene fiber are mixed evenly, the mixture A is added and stirred evenly, and finally barium sulfate is added and mixed evenly to obtain a modified reinforcing fiber.

[0035] The solid-to-liquid ratio of water, polyvinyl alcohol and hydroxypropyl methylcellulose ether in the mixture A is 1L:15g:10g.

[0036] The solid-liquid ratio of the mixture A, steel fiber, polypropylene fiber and barium sulfate is 2L:2kg:1kg:0.5kg.

[0037] The preparation method of the modified coal gangue is:

[0038] The coal gangue is crushed, soaked in a 2 mol / L sulfuric acid solution for 1-2 hours to remove impurities, washed with deionized water after soaking, dried, and then calcined at 800°C for 2 hours to obtain modified coal gangue.

[0039] The foaming agent contains 6 parts of lauryl glucoside, 2 parts of tea saponin, 3 parts of castor oil polyoxyethylene ether, 3 parts of fatty alcohol polyoxyethylene ether sulfonate, 5 parts of sorbitan trioleate and 60 parts of water.

[0040] The foam stabilizer contains 5 parts of sodium alginate, 3 parts of citric acid and 10 parts of cocamidopropylamine oxide.

[0041] A method for preparing lightweight concrete comprises the following steps:

[0042] S1: adding water, lauryl glucoside, tea saponin, castor oil polyoxyethylene ether, fatty alcohol polyoxyethylene ether sulfonate and sorbitan trioleate into a reaction kettle in sequence at a stirring speed of 100-150 rpm, stirring for 8-10 minutes, adding the stirred mixed solution into a pressure foaming machine, starting the pressure foaming machine for foaming, and when the foam is uniform and fine in a hook shape, the foaming agent is obtained and is ready for use;

[0043] S2: putting water, cement, ceramsite, fly ash, modified coal gangue and lightweight aggregate into a mixer and stirring to obtain cement slurry, and then adding modified reinforcing fiber and stirring to obtain mixed slurry;

[0044] S3: adding a foaming agent and a foam stabilizer to the mixed slurry of step S2, and stirring evenly to obtain a lightweight concrete.

[0045] Example 2

[0046] A lightweight concrete is prepared from the following raw materials in parts by weight: 240 parts of cement, 20 parts of fly ash, 70 parts of ceramsite, 50 parts of lightweight aggregate, 80 parts of modified reinforcing fiber, 80 parts of modified coal gangue, 25 parts of foaming agent, 17 parts of foam stabilizer, and 170 parts of water.

[0047] The lightweight aggregate is pumice and volcanic slag; the expanded clay is lightweight shale expanded clay; and the cement is 42.5 grade ordinary Portland cement.

[0048] The preparation method of the modified reinforced fiber is:

[0049] After polyvinyl alcohol and hydroxypropyl methylcellulose ether are mixed evenly, water heated to 60° C. is poured into the mixture, stirred evenly, and then cooled to room temperature to obtain a mixture A; after steel fiber and polypropylene fiber are mixed evenly, the mixture A is added and stirred evenly, and finally barium sulfate is added and mixed evenly to obtain a modified reinforcing fiber.

[0050] The solid-to-liquid ratio of water, polyvinyl alcohol and hydroxypropyl methylcellulose ether in the mixture A is 1L:15g:10g.

[0051] The solid-liquid ratio of the mixture A, steel fiber, polypropylene fiber and barium sulfate is 2L:2kg:1kg:0.5kg.

[0052] The preparation method of the modified coal gangue is:

[0053] The coal gangue is crushed, soaked in a 2 mol / L sulfuric acid solution for 1-2 hours to remove impurities, washed with deionized water after soaking, dried, and then calcined at 800°C for 2 hours to obtain modified coal gangue.

[0054] The foaming agent contains 7 parts of lauryl glucoside, 3 parts of tea saponin, 4 parts of castor oil polyoxyethylene ether, 5 parts of fatty alcohol polyoxyethylene ether sulfonate, 6 parts of sorbitan trioleate and 65 parts of water.

[0055] The foam stabilizer contains 7 parts of sodium alginate, 4 parts of citric acid and 11 parts of cocamidopropylamine oxide.

[0056] A method for preparing lightweight concrete comprises the following steps:

[0057] S1: adding water, lauryl glucoside, tea saponin, castor oil polyoxyethylene ether, fatty alcohol polyoxyethylene ether sulfonate and sorbitan trioleate into a reaction kettle in sequence at a stirring speed of 100-150 rpm, stirring for 8-10 minutes, adding the stirred mixed solution into a pressure foaming machine, starting the pressure foaming machine for foaming, and when the foam is uniform and fine in a hook shape, the foaming agent is obtained and is ready for use;

[0058] S2: putting water, cement, ceramsite, fly ash, modified coal gangue and lightweight aggregate into a mixer and stirring to obtain cement slurry, and then adding modified reinforcing fiber and stirring to obtain mixed slurry;

[0059] S3: adding a foaming agent and a foam stabilizer to the mixed slurry of step S2, and stirring evenly to obtain a lightweight concrete.

[0060] Example 3

[0061] A lightweight concrete is prepared from the following raw materials in parts by weight: 300 parts of cement, 25 parts of fly ash, 80 parts of ceramsite, 60 parts of lightweight aggregate, 100 parts of modified reinforcing fiber, 90 parts of modified coal gangue, 30 parts of foaming agent, 20 parts of foam stabilizer, and 200 parts of water.

[0062] The lightweight aggregate is pumice and volcanic slag; the expanded clay is lightweight shale expanded clay; and the cement is 42.5 grade ordinary Portland cement.

[0063] The preparation method of the modified reinforced fiber is:

[0064] After polyvinyl alcohol and hydroxypropyl methylcellulose ether are mixed evenly, water heated to 60° C. is poured into the mixture, stirred evenly, and then cooled to room temperature to obtain a mixture A; after steel fiber and polypropylene fiber are mixed evenly, the mixture A is added and stirred evenly, and finally barium sulfate is added and mixed evenly to obtain a modified reinforcing fiber.

[0065] The solid-to-liquid ratio of water, polyvinyl alcohol and hydroxypropyl methylcellulose ether in the mixture A is 1L:15g:10g.

[0066] The solid-liquid ratio of the mixture A, steel fiber, polypropylene fiber and barium sulfate is 2L:2kg:1kg:0.5kg.

[0067] The preparation method of the modified coal gangue is:

[0068] The coal gangue is crushed, soaked in a 2 mol / L sulfuric acid solution for 1-2 hours to remove impurities, washed with deionized water after soaking, dried, and then calcined at 800°C for 2 hours to obtain modified coal gangue.

[0069] The foaming agent contains 8 parts of lauryl glucoside, 5 parts of tea saponin, 6 parts of castor oil polyoxyethylene ether, 7 parts of fatty alcohol polyoxyethylene ether sulfonate, 8 parts of sorbitan trioleate and 70 parts of water.

[0070] The foam stabilizer contains 10 parts of sodium alginate, 5 parts of citric acid and 12 parts of cocamidopropylamine oxide.

[0071] A method for preparing lightweight concrete comprises the following steps:

[0072] S1: adding water, lauryl glucoside, tea saponin, castor oil polyoxyethylene ether, fatty alcohol polyoxyethylene ether sulfonate and sorbitan trioleate into a reaction kettle in sequence at a stirring speed of 100-150 rpm, stirring for 8-10 minutes, adding the stirred mixed solution into a pressure foaming machine, starting the pressure foaming machine for foaming, and when the foam is uniform and fine in a hook shape, the foaming agent is obtained and is ready for use;

[0073] S2: putting water, cement, ceramsite, fly ash, modified coal gangue and lightweight aggregate into a mixer and stirring to obtain cement slurry, and then adding modified reinforcing fiber and stirring to obtain mixed slurry;

[0074] S3: adding a foaming agent and a foam stabilizer to the mixed slurry of step S2, and stirring evenly to obtain a lightweight concrete.

[0075] Comparative Example 1

[0076] A lightweight concrete is prepared from the following raw materials in parts by weight: 300 parts of cement, 25 parts of fly ash, 80 parts of ceramsite, 60 parts of lightweight aggregate, 100 parts of reinforcing fiber, 90 parts of modified coal gangue, 30 parts of foaming agent, 20 parts of foam stabilizer, and 150 parts of water.

[0077] The lightweight aggregate is pumice and volcanic slag; the expanded clay is lightweight shale expanded clay; and the cement is 42.5 grade ordinary Portland cement.

[0078] The preparation method of the modified coal gangue is:

[0079] The coal gangue is crushed, soaked in a 2 mol / L sulfuric acid solution for 1-2 hours to remove impurities, washed with deionized water after soaking, dried, and then calcined at 800°C for 2 hours to obtain modified coal gangue.

[0080] The foaming agent contains 8 parts of lauryl glucoside, 5 parts of tea saponin, 6 parts of castor oil polyoxyethylene ether, 7 parts of fatty alcohol polyoxyethylene ether sulfonate, 8 parts of sorbitan trioleate and 70 parts of water.

[0081] The foam stabilizer contains 10 parts of sodium alginate, 5 parts of citric acid and 12 parts of cocamidopropylamine oxide.

[0082] A method for preparing lightweight concrete comprises the following steps:

[0083] S1: adding water, lauryl glucoside, tea saponin, castor oil polyoxyethylene ether, fatty alcohol polyoxyethylene ether sulfonate and sorbitan trioleate into a reaction kettle in sequence at a stirring speed of 100-150 rpm, stirring for 8-10 minutes, adding the stirred mixed solution into a pressure foaming machine, starting the pressure foaming machine for foaming, and when the foam is uniform and fine in a hook shape, the foaming agent is obtained and is ready for use;

[0084] S2: putting water, cement, ceramsite, fly ash, modified coal gangue and lightweight aggregate into a mixer and stirring to obtain cement slurry, and then adding reinforcing fiber and stirring to obtain mixed slurry;

[0085] S3: adding a foaming agent and a foam stabilizer to the mixed slurry of step S2, and stirring evenly to obtain a lightweight concrete.

[0086] Compared with Example 3, this comparative example is the same as Example 3 except that the reinforcing fiber is not modified. The other raw materials and steps are the same as Example 3.

[0087] Comparative Example 2

[0088] A lightweight concrete is prepared from the following raw materials in parts by weight: 300 parts of cement, 25 parts of fly ash, 80 parts of ceramsite, 60 parts of lightweight aggregate, 100 parts of modified reinforcing fiber, 90 parts of modified coal gangue, 30 parts of foaming agent, 20 parts of foam stabilizer, and 150 parts of water.

[0089] The lightweight aggregate is pumice and volcanic slag; the expanded clay is lightweight shale expanded clay; and the cement is 42.5 grade ordinary Portland cement.

[0090] The preparation method of the modified reinforced fiber is:

[0091] After polyvinyl alcohol and hydroxypropyl methylcellulose ether are mixed evenly, water heated to 60° C. is poured into the mixture, stirred evenly, and then cooled to room temperature to obtain a mixture A; after steel fiber and polypropylene fiber are mixed evenly, the mixture A is added and stirred evenly, and finally barium sulfate is added and mixed evenly to obtain a modified reinforcing fiber.

[0092] The solid-to-liquid ratio of water, polyvinyl alcohol and hydroxypropyl methylcellulose ether in the mixture A is 1L:15g:10g.

[0093] The solid-liquid ratio of the mixture A, steel fiber, polypropylene fiber and barium sulfate is 2L:2kg:1kg:0.5kg.

[0094] The preparation method of the modified coal gangue is:

[0095] The coal gangue is crushed, soaked in a 2 mol / L sulfuric acid solution for 1-2 hours to remove impurities, washed with deionized water after soaking, dried, and then calcined at 800°C for 2 hours to obtain modified coal gangue.

[0096] The foaming agent contains 10 parts of lauryl glucoside, 7 parts of tea saponin, 8 parts of castor oil polyoxyethylene ether, 9 parts of fatty alcohol polyoxyethylene ether sulfonate and 70 parts of water.

[0097] The foam stabilizer contains 10 parts of sodium alginate, 5 parts of citric acid and 12 parts of cocamidopropylamine oxide.

[0098] A method for preparing lightweight concrete comprises the following steps:

[0099] S1: adding water, lauryl glucoside, tea saponin, castor oil polyoxyethylene ether, and fatty alcohol polyoxyethylene ether sulfonate to a reaction kettle in sequence at a stirring speed of 100-150 rpm, stirring for 8-10 minutes, adding the stirred mixed solution to a pressure foaming machine, starting the pressure foaming machine for foaming, and when the foam is uniform and fine in a hook shape, the foaming agent is obtained and is ready for use;

[0100] S2: putting water, cement, ceramsite, fly ash, modified coal gangue and lightweight aggregate into a mixer and stirring to obtain cement slurry, and then adding modified reinforcing fiber and stirring to obtain mixed slurry;

[0101] S3: adding a foaming agent and a foam stabilizer to the mixed slurry of step S2, and stirring evenly to obtain a lightweight concrete.

[0102] Compared with Example 3, this comparative example does not add sorbitan trioleate and maintains the total amount of the effective ingredient of the foaming agent unchanged, and the other raw materials and steps are the same as those of Example 3.

[0103] Comparative Example 3

[0104] A lightweight concrete is prepared from the following raw materials in parts by weight: 300 parts of cement, 25 parts of fly ash, 80 parts of ceramsite, 60 parts of lightweight aggregate, 100 parts of modified reinforcing fiber, 90 parts of modified coal gangue, 30 parts of foaming agent, 20 parts of foam stabilizer, and 150 parts of water.

[0105] The lightweight aggregate is pumice and volcanic slag; the expanded clay is lightweight shale expanded clay; and the cement is 42.5 grade ordinary Portland cement.

[0106] The preparation method of the modified reinforced fiber is:

[0107] After polyvinyl alcohol and hydroxypropyl methylcellulose ether are mixed evenly, water heated to 60° C. is poured into the mixture, stirred evenly, and then cooled to room temperature to obtain a mixture A; after steel fiber and polypropylene fiber are mixed evenly, the mixture A is added and stirred evenly, and finally barium sulfate is added and mixed evenly to obtain a modified reinforcing fiber.

[0108] The solid-to-liquid ratio of water, polyvinyl alcohol and hydroxypropyl methylcellulose ether in the mixture A is 1L:15g:10g.

[0109] The solid-liquid ratio of the mixture A, steel fiber, polypropylene fiber and barium sulfate is 2L:2kg:1kg:0.5kg.

[0110] The preparation method of the modified coal gangue is:

[0111] The coal gangue is crushed, soaked in a 2 mol / L sulfuric acid solution for 1-2 hours to remove impurities, washed with deionized water after soaking, dried, and then calcined at 800°C for 2 hours to obtain modified coal gangue.

[0112] The foaming agent contains 7 parts of tea saponin, 8 parts of castor oil polyoxyethylene ether, 9 parts of fatty alcohol polyoxyethylene ether sulfonate, 10 parts of sorbitan trioleate and 70 parts of water.

[0113] The foam stabilizer contains 10 parts of sodium alginate, 5 parts of citric acid and 12 parts of cocamidopropylamine oxide.

[0114] A method for preparing lightweight concrete comprises the following steps:

[0115] S1: adding water, tea saponin, castor oil polyoxyethylene ether, fatty alcohol polyoxyethylene ether sulfonate and sorbitan trioleate into a reaction kettle in sequence at a stirring speed of 100-150rpm, stirring for 8-10 minutes, adding the stirred mixed solution into a pressure foaming machine, starting the pressure foaming machine for foaming, and when the foam is uniform and fine in a hook shape, the foaming agent is obtained and is ready for use;

[0116] S2: putting water, cement, ceramsite, fly ash, modified coal gangue and lightweight aggregate into a mixer and stirring to obtain cement slurry, and then adding modified reinforcing fiber and stirring to obtain mixed slurry;

[0117] S3: adding a foaming agent and a foam stabilizer to the mixed slurry of step S2, and stirring evenly to obtain a lightweight concrete.

[0118] Compared with Example 3, this comparative example does not add lauryl glucoside and maintains the total amount of the effective ingredient of the foaming agent unchanged, and the other raw materials and steps are the same as those of Example 3.

[0119] Comparative Example 4

[0120] A lightweight concrete is prepared from the following raw materials in parts by weight: 300 parts of cement, 25 parts of fly ash, 80 parts of ceramsite, 60 parts of lightweight aggregate, 100 parts of modified reinforcing fiber, 90 parts of modified coal gangue, 30 parts of foaming agent, and 150 parts of water.

[0121] The lightweight aggregate is pumice and volcanic slag; the expanded clay is lightweight shale expanded clay; and the cement is 42.5 grade ordinary Portland cement.

[0122] The preparation method of the modified reinforced fiber is:

[0123] After polyvinyl alcohol and hydroxypropyl methylcellulose ether are mixed evenly, water heated to 60° C. is poured into the mixture, stirred evenly, and then cooled to room temperature to obtain a mixture A; after steel fiber and polypropylene fiber are mixed evenly, the mixture A is added and stirred evenly, and finally barium sulfate is added and mixed evenly to obtain a modified reinforcing fiber.

[0124] The solid-to-liquid ratio of water, polyvinyl alcohol and hydroxypropyl methylcellulose ether in the mixture A is 1L:15g:10g.

[0125] The solid-liquid ratio of the mixture A, steel fiber, polypropylene fiber and barium sulfate is 2L:2kg:1kg:0.5kg.

[0126] The preparation method of the modified coal gangue is:

[0127] The coal gangue is crushed, soaked in a 2 mol / L sulfuric acid solution for 1-2 hours to remove impurities, washed with deionized water after soaking, dried, and then calcined at 800°C for 2 hours to obtain modified coal gangue.

[0128] The foaming agent contains 8 parts of lauryl glucoside, 5 parts of tea saponin, 6 parts of castor oil polyoxyethylene ether, 7 parts of fatty alcohol polyoxyethylene ether sulfonate, 8 parts of sorbitan trioleate and 70 parts of water.

[0129] A method for preparing lightweight concrete comprises the following steps:

[0130] S1: adding water, lauryl glucoside, tea saponin, castor oil polyoxyethylene ether, fatty alcohol polyoxyethylene ether sulfonate and sorbitan trioleate into a reaction kettle in sequence at a stirring speed of 100-150 rpm, stirring for 8-10 minutes, adding the stirred mixed solution into a pressure foaming machine, starting the pressure foaming machine for foaming, and when the foam is uniform and fine in a hook shape, the foaming agent is obtained and is ready for use;

[0131] S2: putting water, cement, ceramsite, fly ash, modified coal gangue and lightweight aggregate into a mixer and stirring to obtain cement slurry, and then adding modified reinforcing fiber and stirring to obtain mixed slurry;

[0132] S3: adding a foaming agent to the mixed slurry of step S2, and stirring evenly to obtain lightweight concrete.

[0133] Compared with Example 3, this comparative example is the same as Example 3 except that the foam stabilizer is not added.

[0134] Performance Testing

[0135] The lightweight concrete samples prepared in Examples 1-3 and Comparative Examples 1-4 were subjected to compressive strength test, flexural strength test, thermal conductivity test and water absorption test.

[0136] The mechanical strength and water absorption rate were tested according to JG / T266-2011 “Foamed Concrete”, and the thermal conductivity was tested according to GB / T10294-2008 “Determination of Steady-State Thermal Resistance and Related Properties of Insulating Materials - Guarded Hot Plate Method”. The measured data are shown in Table 1.

[0137] Micro performance test:

[0138] Sample preparation for observing the microscopic surface morphology of lightweight concrete samples: The concrete samples of Example 3 and Comparative Examples 1-4 were chopped into cubes with a side length not exceeding 5 mm, and then the cube samples were placed in a vacuum drying oven and dried to constant weight with the temperature set to 60±5°C, and finally SEM testing was performed.

[0139] SEM was used to determine the microscopic morphology of four groups of foam concrete samples, such as Figure 1 As shown (Note: A is the SEM image of Example 3; B is the SEM image of Comparative Example 1; C is the SEM image of Comparative Example 2; D is the SEM image of Comparative Example 3; E is the SEM image of Comparative Example 4), the foam surface of the lightweight concrete sample of Example 3 of the present invention becomes smooth and complete, while the lightweight concretes of Comparative Examples 1-4 have varying degrees of incomplete holes and pores and cracks.

[0140] Table 1 Test results

[0141]

[0142]

[0143] It can be seen from the data in Table 1 that the compressive strength of the lightweight concrete prepared in Examples 1-3 of the present application reaches 10.9-11.6 MPa, the flexural strength reaches 1.77-1.85 MPa, the thermal conductivity reaches 0.037-0.041 W / (mK), and the water absorption rate reaches less than 1.75%, indicating that the lightweight concrete prepared by the present invention has high strength, good thermal insulation effect and low water absorption rate.

[0144] As can be seen from Comparative Example 1, the reinforcing fibers in Comparative Example 1 are not modified, and the various properties of the prepared concrete are significantly reduced. This may be due to the poor adhesion of the unmodified reinforcing fibers in the cement slurry, which reduces the fusion with the cement slurry and also reduces the fluidity in the concrete, affecting the uniformity of the foam in the concrete. As can be seen from Comparative Examples 2 and 3, under the premise of reducing the types of nonionic surfactants in the foaming agent in Comparative Examples 2 and 3 and maintaining the total amount of the effective ingredients of the foaming agent unchanged, the performance of the prepared concrete has decreased, indicating that the 5 nonionic surfactants of the present invention have a synergistic effect on the foaming performance and foam stability, and the 5 nonionic surfactants in the foaming agent are indispensable. As can be seen from Comparative Example 4, no foam stabilizer is added in Comparative Example 4, resulting in a significant increase in the thermal insulation coefficient and water absorption, indicating that the foam stabilizer of the present invention has a greater influence on the foam stability.

[0145] It should be noted that the above embodiments are only partial embodiments of the preferred methods of implementing the present invention, rather than all embodiments. Obviously, based on the above embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

Claims

1. A lightweight concrete, characterized in that: The invention is prepared from the following raw materials in parts by weight: 200-300 parts of cement, 15-25 parts of fly ash, 60-80 parts of ceramsite, 50-60 parts of lightweight aggregate, 60-100 parts of modified reinforcing fiber, 70-90 parts of modified coal gangue, 20-30 parts of foaming agent, 15-20 parts of foam stabilizer and 150-200 parts of water.

2. The lightweight concrete according to claim 1, characterized in that: The lightweight aggregate is pumice and volcanic slag; the expanded clay is lightweight shale expanded clay; and the cement is 42.5 grade ordinary Portland cement.

3. The lightweight concrete according to claim 1, characterized in that: The preparation method of the modified reinforced fiber is: After polyvinyl alcohol and hydroxypropyl methylcellulose ether are mixed evenly, water heated to 60° C. is poured into the mixture, stirred evenly, and then cooled to room temperature to obtain a mixture A; after steel fiber and polypropylene fiber are mixed evenly, the mixture A is added and stirred evenly, and finally barium sulfate is added and mixed evenly to obtain a modified reinforcing fiber.

4. The lightweight concrete according to claim 3, characterized in that: The solid-to-liquid ratio of water, polyvinyl alcohol and hydroxypropyl methylcellulose ether in the mixture A is 1L:15g:10g.

5. The lightweight concrete according to claim 3, characterized in that: The solid-liquid ratio of the mixture A, steel fiber, polypropylene fiber and barium sulfate is 2L:2kg:1kg:0.5kg.

6. The lightweight concrete according to claim 1, characterized in that: The preparation method of the modified coal gangue is: The coal gangue is crushed, soaked in a 2 mol / L sulfuric acid solution for 1-2 hours to remove impurities, washed with deionized water after soaking, dried, and then calcined at 800°C for 2 hours to obtain modified coal gangue.

7. The lightweight concrete according to claim 1, characterized in that: The foaming agent contains 6-8 parts of lauryl glucoside, 2-5 parts of tea saponin, 3-6 parts of castor oil polyoxyethylene ether, 3-7 parts of fatty alcohol polyoxyethylene ether sulfonate, 5-8 parts of sorbitan trioleate and 60-70 parts of water.

8. The lightweight concrete according to claim 1, characterized in that: The foam stabilizer contains 5-10 parts of sodium alginate, 3-5 parts of citric acid and 10-12 parts of cocamidopropylamine oxide.

9. A method for preparing the lightweight concrete according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1: adding water, lauryl glucoside, tea saponin, castor oil polyoxyethylene ether, fatty alcohol polyoxyethylene ether sulfonate and sorbitan trioleate into a reaction kettle in sequence at a stirring speed of 100-150 rpm, stirring for 8-10 minutes, adding the stirred mixed solution into a pressure foaming machine, starting the pressure foaming machine for foaming, and when the foam is uniform and fine in a hook shape, the foaming agent is obtained and is ready for use; S2: putting water, cement, ceramsite, fly ash, modified coal gangue and lightweight aggregate into a mixer and stirring to obtain cement slurry, and then adding modified reinforcing fiber and stirring to obtain mixed slurry; S3: adding a foaming agent and a foam stabilizer to the mixed slurry of step S2, and stirring evenly to obtain a lightweight concrete.